2020
DOI: 10.1038/s41467-020-18026-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the TRPV1 S1-S4 membrane domain contributes to thermosensing

Abstract: Sensing and responding to temperature is crucial in biology. The TRPV1 ion channel is a wellstudied heat-sensing receptor that is also activated by vanilloid compounds, including capsaicin. Despite significant interest, the molecular underpinnings of thermosensing have remained elusive. The TRPV1 S1-S4 membrane domain couples chemical ligand binding to the pore domain during channel gating. Here we show that the S1-S4 domain also significantly contributes to thermosensing and couples to heat-activated gating. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…However, as the many intra- and intermolecular contributions to chemical shift vary in complex ways with temperature, a quantitative structural interpretation of TCs has remained elusive. Recent studies in our group and others have shown how the complexities of amide temperature dependencies may be simplified by comparing related protein variants, yielding nuanced information on changes in structural stability and sampling of alternative states significant for natural function, disease, drug discovery, and materials ( 6 , 16 26 ).…”
mentioning
confidence: 99%
“…However, as the many intra- and intermolecular contributions to chemical shift vary in complex ways with temperature, a quantitative structural interpretation of TCs has remained elusive. Recent studies in our group and others have shown how the complexities of amide temperature dependencies may be simplified by comparing related protein variants, yielding nuanced information on changes in structural stability and sampling of alternative states significant for natural function, disease, drug discovery, and materials ( 6 , 16 26 ).…”
mentioning
confidence: 99%
“…As the mutation R557E/A/L or E570L/A can disrupt the stimulatory R557-E570 H-bond, it is reasonable that the R557E or E570L mutant leads to a complete loss of function, or mutants R557A/L and E570A have low heat sensitivity, or E570A increases the threshold from 41.5 °C to 44.3 °C. [22,23] Since the Loop 9 had one equivalent H-bond to seal a minimal 9-residue loop for the open state of rTRPV1 ( Figs. 2, 5A ), it had an upper melting temperature limit 46 °C.…”
Section: Discussionmentioning
confidence: 99%
“…The T407 is located in the membrane proximal domain that has been suggested to be involved heat sensing in TRP channels, 33 although other sites in TRPV1 are also thought to contribute to thermo-sensing. 34 Computer modeling has shown that the T407 site (T406 in rats) specifically resides in a flexible linker within a close proximity to the TRP box. The Cdk5 site, in particular, shows high van der Waals energy differences as the conformation of this linker changes between the TRPV1 open and closed state, all of which suggests that Cdk5 mediated phosphorylation could impact ion channel gating.…”
Section: Discussionmentioning
confidence: 99%